Śiśukiśora sāhityera andaramahala - Senagupta, Candramallī (Pustaka Bipaṇi, 2022)
Critical articles on Bengali children's literature.
Includes bibliographical references
Keywords: Aufsatzsammlung; Children's literature; Bengali; History and criticism.